К вопросу о понятии избыточных функций государственного управления - Ivanenko I. N., Kovalenko E. A. (Relevant lines of scientific research: development prospects, 2017)
The article analyses the concept of excess functions of government. Discusses the concept, characteristic features and ways of development Institute of public administration.
Keywords: государственное управление; избыточные функции; redundant functions; state control